Novel medical polymethyl methacrylate bone cement and preparation method thereof
Modified polymethyl methacrylate bone cement by molybdenum disulfide nanosheets has solved the problem of insufficient biocompatibility and mechanical stability of traditional bone cement, and achieved a multifunctional orthopedic treatment material, suitable for fracture repair and vertebroplasty.
Patent Information
- Application Number
- CN202510392716.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-07-18
Smart Images

Figure SMS_4 
Figure SMS_5 
Figure SMS_6
Abstract
Description
Technical Field
[0001] The present invention relates to the field of medical materials, and particularly to a novel medical polymethyl methacrylate bone cement and a preparation method thereof. Background Art
[0002] Bone cement is a biomaterial used in orthopedic surgeries and treatments, usually composed of biocompatible calcium phosphate ceramic powder and liquid monomers. The main use of bone cement is to fill fractures or bone cavities to provide support and stability and promote fracture healing. However, traditional bone cement has limitations in some aspects, such as tissue damage and tissue infection caused by high temperatures, low biocompatibility, which may lead to long-term mechanical instability and the risk of reoperation. Therefore, the research and development of modified bone cement have become a popular research field.
[0003] Several existing studies have modified and improved the structure, mechanical and biological properties of PMMA bone cement. The focus of these studies is to control the basic parameters of bone cement synthesis, such as polymerization temperature, curing time, compressive strength, flexural modulus. In addition, improving bone reconstruction effect, promoting porosity, enhancing bioactivity, cell viability, increasing osteoblast activity, and enhancing the bonding ability between bone cement and bone are essential parameters for improving the quality of bone cement, and current studies are limited to modifying a single property. Therefore, it is necessary to improve performance in multiple aspects. Summary of the Invention
[0004] To solve the problems of the existing technology, the present invention provides a novel medical polymethyl methacrylate bone cement and a preparation method thereof. The present invention uses molybdenum disulfide as a modifying substance, and the prepared novel medical polymethyl methacrylate bone cement has both antibacterial and osteogenic functions.
[0005] A preparation method of a novel medical polymethyl methacrylate bone cement includes the following steps:
[0006] (1) Dissolve PMMA powder in dimethyl sulfoxide (DMSO) to obtain a PMMA solution;
[0007] (2) Add MoS2 nanosheets to the PMMA solution, and stir the obtained mixture at 78 - 82 °C for 22 - 26 hours to promote the uniform dispersion of MoS2 nanosheets in the PMMA matrix; after the stirring process ends, dry the mixture to obtain a MoS2-PMMA nanocomposite;
[0008] (3) Mix the MoS2-PMMA nanocomposite with MMA liquid evenly, and fill the obtained mixture into a mold for curing and molding to obtain a novel medical polymethyl methacrylate bone cement.
[0009] Further, in step (1), the ratio of PMMA powder to dimethyl sulfoxide in the PMMA solution is 2 g: 50 mL.
[0010] Further, in step (1), the PMMA powder is dissolved in dimethyl sulfoxide (DMSO) and stirred at room temperature for 24 hours to ensure complete dissolution, obtaining a PMMA solution.
[0011] Further, in step (1), the synthesis method of the MoS2 nanosheets includes the following steps:
[0012] Disperse the MoS2 powder in N,N-dimethylformamide (DMF), and the mixture is ultrasonically treated to form a black suspension; subsequently, the suspension is centrifuged in a high-speed centrifuge to collect the thinner MoS2 flakes. The obtained MoS2 flakes are redispersed in N,N-dimethylformamide (DMF), L-cysteine is added to the redispersed mixture, and the mixture is stirred thoroughly to ensure uniform dispersion, and then aged at room temperature for 24 hours; after aging, the mixture is centrifuged again to collect the precipitate, namely MoS2 nanosheets; to remove the unbound L-cysteine and residual DMF, the product is washed with deionized water.
[0013] Further, the concentration of the MoS2 powder in N,N-dimethylformamide (DMF) is 5 mg / mL.
[0014] Further, the final concentration of L-cysteine in the redispersed mixture is 0.1 mg / mL.
[0015] Further, the time of the ultrasonic treatment is 12 hours.
[0016] Further, the suspension is centrifuged in a high-speed centrifuge, and the light yellow supernatant containing the thinner MoS2 flakes is collected for further treatment; to ensure purity, the supernatant of the thinner MoS2 flakes is centrifuged again.
[0017] Further, the centrifugation conditions are: centrifuging at 1200 rpm for 30 minutes.
[0018] Further, the deionized water washing process is accompanied by an additional centrifugation step at 12000 rpm to ensure thorough purification.
[0019] Further, in step (2), the weight percentage of the MoS2 nanosheets in the total amount of MoS2 nanosheets and PMMA powder is 1% - 5%, such as 1%, 2%, 3% and 5%.
[0020] Further, in step (2), the specific operation of the drying is: pouring the mixture into a petri dish and drying under controlled heating conditions to ensure complete evaporation of DMSO.
[0021] Further, in step (3), a vortex mixer is used to uniformly mix the MoS2-PMMA nanocomposite and MMA liquid at room temperature.
[0022] Further, in step (3), the obtained mixture is filled into a mold and left to stand at room temperature for 25 - 35 min for curing and forming to obtain a novel medical polymethyl methacrylate bone cement.
[0023] Further, the formulation of the novel medical polymethyl methacrylate bone cement is prepared using a powder-liquid mixing system, including MMA liquid and MoS2-PMMA nanocomposite. Referring to the manufacturer's instructions for preparing PMMMA bone cement, a vortex mixer is used to thoroughly mix the MMA liquid and PMoS2-PMMA nanocomposite at room temperature, followed by curing and forming to prepare novel medical PMMA bone cement samples. The formulation of the PMMA bone cement is prepared using a powder-liquid mixing system, including MMA liquid and PMMA powder. According to the manufacturer's instructions, a vortex mixer is used to thoroughly mix the MMA liquid and PMMA powder at room temperature, followed by curing and forming to prepare PMMA bone cement samples.
[0024] The core of the present invention lies in developing a novel MoS2-PMMA nanocomposite and systematically evaluating its performance in terms of mechanical properties, antibacterial properties, and osteogenic ability, etc. First, MoS2 nanosheets were synthesized by a chemical method, and ultrasonic dispersion and centrifugation were used to ensure the purity and dispersion of the MoS2 nanosheets. Then, the MoS2 nanosheets were incorporated into PMMA bone cement to prepare MoS2-PMMA composites with different MoS2 contents. To evaluate its mechanical properties, tensile tests and compression tests were carried out to determine the effects of different MoS2 concentrations on mechanical indexes such as the elastic modulus and compressive strength of PMMA. In addition, finite element analysis was used to simulate the stress distribution of the spine after vertebroplasty to further evaluate the stability and performance of the composite under physiological conditions. The osteogenic experiment used the MC3T3-E1 pre-osteoblast cell line, and the CCK-8 kit, alkaline phosphatase (ALP) staining, and alizarin red S (ARS) staining were used to evaluate the promoting effects of the material on the proliferation, differentiation, and mineralization of osteoblasts. The antibacterial experiment tested the antibacterial effects of MoS2-PMMA composites with different MoS2 contents through the inhibition experiment against Escherichia coli.
[0025] The research results show that the mechanical properties of the MoS2-PMMA nanocomposite are significantly improved. Through tensile tests, it was found that the elastic modulus of the MoS2-PMMA composite gradually decreases with the increase in the MoS2 content. The elastic modulus of the 5% MoS2-PMMA composite is the lowest, reaching 2100.1 ± 29.7 MPa, which is much lower than that of pure PMMA (2706.1 ± 14.7 MPa, P < 0.05). This result indicates that the introduction of MoS2 nanosheets effectively enhances the mechanical properties of PMMA, enabling it to better withstand stress under load conditions and meet the clinical requirements in orthopedic surgeries. The results of finite element analysis further verify this. The simulation results show that the stress distribution pattern of the MoS2-PMMA composite under different physiological states is similar to that of pure PMMA, indicating that its stability in vertebroplasty has no significant change.
[0026] Advantages of the present invention:
[0027] In the present invention, molybdenum disulfide nanosheets are used as the modifying substance. The prepared MoS2-PMMA nanocomposite has significantly improved mechanical properties, osteogenic activity, and antibacterial properties, providing a multifunctional innovative material for orthopedic treatment. By adding MoS2, not only the mechanical stability of PMMA is enhanced, but also its antibacterial property is effectively improved, and the growth, differentiation, and mineralization of bone cells are promoted. These results indicate that the MoS2-PMMA composite has good prospects in clinical orthopedic applications, especially suitable for treatments such as fracture repair and vertebroplasty, and can effectively reduce the risk of postoperative infection and promote bone healing.
[0028] The effects achieved by the present invention are multiple, and the single-sided effects are more advantageous compared to other products. Description of the drawings
[0029] Figure 1 It is a physical picture of bone cement.
[0030] Figure 2 It is a finite element model. Among them, (a) sagittal plane of the ligament, (b) overall view of the ligament, (c) rear view of the ligament, (d) cross-sectional view of the ligament, (e) cross-sectional view of the mesh, (f) cortical bone and cancellous bone models.
[0031] Figure 3Von Mises stress distribution diagrams of the T11 vertebral body during forward flexion (upper left), extension (upper right), lateral bending (lower left), rotation (lower right), and testing when implanting bone cement. Among them, a is the Von Mises stress distribution diagram of the T11 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting PMMA bone cement, b is the Von Mises stress distribution diagram of the T11 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting 1% MoS2-PMMA bone cement, c is the Von Mises stress distribution diagram of the T11 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting 3% MoS2-PMMA bone cement, d is the Von Mises stress distribution diagram of the T11 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting 5% MoS2-PMMA bone cement, unit: megapascal (MPA).
[0032] Figure 4 Von Mises stress distribution diagrams of the T12 vertebral body during forward flexion (upper left), extension (upper right), lateral bending (lower left), rotation (lower right), and testing when implanting bone cement. Among them, a is the Von Mises stress distribution diagram of the T12 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting PMMA bone cement, b is the Von Mises stress distribution diagram of the T12 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting 1% MoS2-PMMA bone cement, c is the Von Mises stress distribution diagram of the T12 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting 3% MoS2-PMMA bone cement, d is the Von Mises stress distribution diagram of the T12 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting 5% MoS2-PMMA bone cement, unit: megapascal (MPA).
[0033] Figure 5 Von Mises stress distribution diagrams of the L1 vertebral body during forward flexion (upper left), extension (upper right), lateral bending (lower left), rotation (lower right), and testing when implanting bone cement. Among them, a is the Von Mises stress distribution diagram of the L1 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting PMMA bone cement, b is the Von Mises stress distribution diagram of the L1 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting 1% MoS2-PMMA bone cement, c is the Von Mises stress distribution diagram of the L1 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting 3% MoS2-PMMA bone cement, d is the Von Mises stress distribution diagram of the L1 vertebral body during forward flexion, extension, lateral bending, rotation, and testing when implanting 5% MoS2-PMMA bone cement, unit: megapascal (MPA).
[0034] Figure 6Respectively represent the proliferation of MC3T3-E1 osteoblasts on the 1st, 3rd, and 5th days.
[0035] Figure 7 Show the microscopic conditions and alkaline phosphatase activities of MC3T3-E1 on the 7th and 14th days in pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA. Among them, a shows the microscopic conditions of MC3T3-E1 on the 7th and 14th days in pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA, b shows the alkaline phosphatase activity of MC3T3-E1 on the 7th day in pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA, and c shows the alkaline phosphatase activity of MC3T3-E1 on the 14th day in pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA.
[0036] Figure 8 Show the microscopic conditions of ars staining and calcium salt deposition of MC3T3-E1 on the 14th and 21st days in pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA. Among them, a shows the microscopic conditions of ars staining of MC3T3-E1 on the 14th and 21st days in pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA, b shows the calcium salt deposition of MC3T3-E1 on the 14th day in pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA, and c shows the calcium salt deposition of MC3T3-E1 on the 21st day in pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA.
[0037] Figure 9 Show the colony growth of pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA on agar plates at 8 hours, 16 hours, and 24 hours. Among them, a shows the colony growth of pure PMMA on agar plates at 8 hours, 16 hours, and 24 hours from left to right. b shows the colony growth of 1% MoS2-PMMA on agar plates at 8 hours, 16 hours, and 24 hours from left to right. c shows the colony growth of 3% MoS2-PMMA on agar plates at 8 hours, 16 hours, and 24 hours from left to right. d shows the colony growth of 5% MoS2-PMMA on agar plates at 8 hours, 16 hours, and 24 hours.
[0038] Figure 10The number of colonies for 24-hour pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA. Detailed implementation manners
[0039] The following non-limiting examples can enable those of ordinary skill in the art to more comprehensively understand the present invention, but do not limit the present invention in any way.
[0040] In the following examples, SPSS 21.0 was used for statistical analysis of data. The results are expressed as mean ± standard deviation (SD). One-way analysis of variance (ANOVA) was used for statistical analysis. For the comparison of multiple group means, a significance level of P < 0.05 was used to determine statistical significance.
[0041] Example 1 Preparation of MoS2-PMMA bone cement
[0042] (1) Synthesis of MoS2 nanosheets
[0043] MoS2 powder (Aldrich, 69860) was carefully dispersed in N,N-dimethylformamide (DMF) (Aldrich, 319937) to a concentration of 5 mg / mL. The mixture was sonicated for 12 hours to form a black suspension. Subsequently, the suspension was centrifuged at 4000 rpm for 30 minutes in a high-speed centrifuge. The pale yellow supernatant containing thinner MoS2 flakes was collected for further processing. To ensure purity, the collected supernatant was centrifuged again at 12000 rpm for 30 minutes. The resulting precipitate was redispersed in an equal volume of fresh DMF. At this stage, L-cysteine (Aldrich, 168149) was added to the redispersed mixture to a final concentration of 0.1 mg / mL. The mixture was stirred thoroughly to ensure uniform dispersion and then aged at room temperature for 24 hours. After aging, the mixture was centrifuged again at 12000 rpm for 30 minutes to collect the precipitate, i.e., MoS2 nanosheets. To remove unbound L-cysteine and residual DMF, the product was extensively washed with deionized water. The washing process was accompanied by an additional centrifugation step at 12000 rpm to ensure thorough purification.
[0044] (2) Preparation of PMMA bone cement
[0045] The formulation of PMMA was prepared using a powder-liquid mixing system. Among them, methyl methacrylate (MMA) liquid, as the liquid component, is a commonly used organic monomer with good chemical activity and fluidity. PMMA powder, as the solid component, is the polymer form of MMA and exhibits excellent mechanical properties and biocompatibility. Both were used directly without any modification. According to According to the manufacturer's instructions, MMA liquid and PMMA bone cement powder were thoroughly mixed at room temperature using a vortex mixer until a dough-like consistency was achieved, and the resulting mixture was filled into a mold and cured (standing at room temperature for 30 minutes) to prepare PMMA bone cement samples. The mixing was carried out strictly in accordance with the ratios or percentages specified in Table 1.
[0046] Table 1 Composition and content of PMMA bone cement
[0047]
[0048] (3) Synthesis of MoS2-PMMA nanocomposites
[0049] To synthesize MoS2-PMMA nanocomposites, 2 grams of PMMA powder (powder in PMMA bone cement formula) was dissolved in 50 mL of dimethyl sulfoxide (DMSO) (Aldrich, 472301) and stirred vigorously at room temperature for 24 hours to ensure complete dissolution. Subsequently, different weight percentages of MoS2 nanosheets (1%, 2%, 3% and 5%) were introduced into the PMMA solution. The resulting mixture was stirred at 80°C for another 24 hours to promote uniform dispersion of MoS2 nanosheets in the PMMA matrix. After the stirring process, the mixture was poured into a petri dish and dried under controlled heating conditions to ensure complete evaporation of DMSO. At this point, the MoS2-PMMA nanocomposite has been prepared for further analysis.
[0050] (4) Preparation of MoS2-PMMA bone cement
[0051] The polymethyl methacrylate in the formula of PMMA bone cement in step (2) is replaced with the MoS2-PMMA nanocomposite prepared in step (3) to prepare MoS2-PMMA bone cement, that is, the MMA liquid and the MoS2-modified PMMA bone cement powder are thoroughly mixed at room temperature using a vortex mixer until a dough-like consistency is reached, and the resulting mixture is filled into a mold for solidification (standing at room temperature for 30 minutes) to prepare a MoS2-PMMA bone cement sample.
[0052] Example 2 Mechanical properties of bone cement
[0053] (1) Mechanical properties test of bone cement
[0054] Before the experiment, the laboratory temperature was set to 23 °C, and the test equipment and experimental reagents were equilibrated at (23 ± 1) °C for 2 hours. Mechanical analysis was performed using a universal testing machine (AG-X100KN, Shimadzu, Kyoto, Japan) equipped with 100N and 1000N load cells. Each group of PMMA bone cement powder and liquid was uniformly mixed according to the method in Example 1 until a dough-like consistency was achieved, and then the mixture was filled into the mold holes and left to stand at room temperature for 30 min to prepare PMMA bone cement and MoS2-PMMA bone cement samples. All test samples were cylindrical (gauge length 12 mm, width 6 mm, conforming to ISO 5833 standard). The thickness of the samples was evaluated using a caliper, and the average value was 1 mm. The uniaxial tensile speed was set to 20 mm / min. For each composition, 10 samples were tested in total, and the elastic modulus (in MPa) was determined using QMAT software and averaged.
[0055] (2) Elastic modulus analysis of various MoS2-PMMA composites
[0056] The elastic moduli of pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA were 2706.1 ± 14.7 MPa, 2598.6 ± 32.4 MPa, 2312.2 ± 25.5 MPa, and 2100.1 ± 29.7 MPa, respectively (Table 2). As the weight percentage of MoS2 nanosheets incorporated increased, the elastic modulus of the MoS2-PMMA nanocomposites increased significantly (P value < 0.05).
[0057] Table 2 Summary of elastic modulus data
[0058]
[0059] Example 3 Finite element analysis
[0060] (1) Establishment and analysis of a finite element model of the T11-L1 vertebral body
[0061] Spinal CT data were obtained from a healthy male volunteer (70 kg, 175 cm) with no history of spinal trauma or osteoporosis. This study was approved by the Ethics Committee of our hospital, and the volunteer provided informed consent.
[0062] Using the DICOM format data file, we accurately imported the CT-scanned spinal data into MIMICS software for three-dimensional (3D) model reconstruction to ensure the accuracy and integrity of the model. Subsequently, the reconstructed 3D model was imported into Geomagic Studio 2024 in STL format for reverse engineering. By surface smoothing, cortical bone and cancellous bone separation, noise reduction, and surface fitting, we significantly improved the accuracy and realism of the model.
[0063] The optimized 3D geometric model is exported in STP format and imported into SolidWorks 2024 for detailed assembly of the vertebral body. Using the loft and split functions, we carefully trim and combine cortical bone and cancellous bone while constructing key structures such as the lumbar intervertebral disc, annulus fibrosus, nucleus pulposus, endplate, articular cartilage, and adding linear ligaments including the anterior longitudinal ligament, posterior longitudinal ligament, interspinous ligament, supraspinous ligament, ligamentum flavum, intertransverse ligament, and capsular ligament. Regarding bone cement, general data indicate that the volume of bone cement injection is usually 6 ml, but clinically, 3 - 4 ml is usually injected. However, a recent study shows that vertebral bodies injected with 6 ml of bone cement have stronger spinal strength than those injected with 3 - 4 ml. Therefore, this study uses the data of 6 ml of bone cement( Figure 2 )
[0064] The cortical bone thickness of the vertebral body is set to 1 mm, and the endplate thickness is also set to 1 mm. The articular cartilage is set to 0.3 mm. The intervertebral disc consists of the nucleus pulposus and the outer annulus. The volume of the nucleus pulposus is set to about 40% of the total area of the intervertebral disc. The material properties and assignments of the remaining finite element model are shown in Tables 3 and 4. After completing the 3D model construction, we import it into ANSYS Workbench 24.2 for in - depth finite element analysis. We perform a fine tetrahedral mesh division on the vertebra, vertebral body, endplate, and intervertebral disc. The mesh size of the articular cartilage is 0.5 mm to accurately capture its stress distribution, and the mesh size of the remaining parts is 1 mm to balance calculation accuracy and efficiency
[26] . The spine and intervertebral disc are analyzed as independent entities, and the tetrahedral 10 - node element type is selected to accurately simulate their complex loading conditions. For ligaments, we use the LINK180 element type, only considering their tensile properties to simplify the calculation and improve efficiency.
[0065] Table 3 Ligament stiffness values (unit: N / m)
[0066]
[0067] Table 4 Property values of each part of the vertebral body
[0068]
[0069]
[0070] To comprehensively simulate the load conditions of the human spine in various states, we applied actual loads to the finite element model. Specifically, an axial compressive load of 300 N was applied to the upper surface of the T11 vertebral body to simulate the pressure borne by the spine during standing. In addition, we simulated four spinal motion states: flexion, extension, lateral bending, and rotation, and applied these states to the models injected with four different types of 4 mL bone cement (pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, 5% MoS2-PMMA).
[0071] (2) Stress distribution on the surface of adjacent vertebral bodies induced by MoS2-PMMA
[0072] After constructing the finite element models of the T11-L1 vertebral bodies filled with different types of bone cement, we found that the maximum von Mises stress values generated by pure PMMA on the T11 vertebral body under flexion, extension, left lateral bending, and right lateral bending states were 2.788 MPa, 3.684 MPa, 3.101 MPa, and 2.185 MPa respectively ( Figure 3 ). This stress distribution pattern was consistent with the stress distribution patterns observed in the 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA groups under the same conditions.
[0073] Similarly, for the T12 vertebral body, the maximum von Mises stress values generated by pure PMMA under the four conditions were 2.303 MPa, 1.463 MPa, 2.912 MPa, and 1.711 MPa. The corresponding stress values in the 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA groups were 2.299 MPa / 1.463 MPa / 2.911 MPa / 1.709 MPa, 2.294 MPa / 1.463 MPa / 2.91 MPa / 1.706 MPa, and 2.293 MPa / 1.463 MPa / 2.909 MPa / 1.705 MPa respectively, which were almost the same as those in the pure PMMA group. This indicates that the decrease in the elastic modulus of MoS2-PMMA bone cement is within a controllable range and can provide a support strength comparable to that of conventional bone cement. In addition, the application of MoS2-PMMA bone cement did not significantly increase the stress distribution in the T12 segment nor elevate the potential risk of fracture. ( Figure 4 )
[0074] For the L1 vertebral body, the maximum von Mises stress values generated by pure PMMA under the four conditions were 2.738 MPa, 1.961 MPa, 2.581 MPa, and 2.381 MPa. This result was also consistent with the results observed in the 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA groups under the same conditions ( Figure 5) Statistical analysis showed that there was no significant difference in the stress distribution on the adjacent vertebral surfaces among different types of MoS2-PMMA bone cements (P value > 0.05).
[0075] Osteogenic performance of the bone cement in Example 4
[0076] (1) Culture of MC3T3-E1 pre-osteoblast cell line
[0077] The MC3T3-E1 cell line, as a model of mouse calvarial osteoblasts, was purchased from ATCC (CRL-2593, Beijing, China). To maintain its normal physiological state, the cells were cultured in a humid atmosphere at a constant temperature of 37 °C with 5% CO2, simulating in vivo conditions. The basal medium was α-minimum essential medium (α-MEM) without ascorbic acid (Aldrich, SLM-244), supplemented with 10% fetal bovine serum (FBS) as a nutrient source, 1% antibiotic-antifungal solution to prevent microbial contamination, and 1 mM sodium pyruvate to optimize cell metabolism. To ensure a stable and fresh growth environment, the medium was changed every 3 to 4 days. During cell proliferation, to prevent contact inhibition caused by overgrowth, when the cell confluence did not reach 80%, trypsin / EDTA solution (9002-07-7 and 60-00-4, Beijing Solarbio Science & Technology Co., Ltd.) was used for subculture to maintain its continuous proliferation ability. In all experimental procedures, MC3T3-E1 cells were seeded on culture dishes at an initial density of 2000 cells / cm 2 and given sufficient time to grow to complete confluence. After reaching this growth stage, the cells were ready for subsequent experimental operations.
[0078] (2) Evaluation of osteoblast viability
[0079] Pure PMMA, 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA were processed into similar shapes and sterilized by CO^60^ irradiation. According to the ISO 10993 standard and the methods reported in the literature, the sterilized samples were incubated in complete medium at a ratio of 0.2 g:1 mL for 48 hours, and then the sterilized samples were removed. The resulting culture medium was used as the extract. Then the extract was transferred to a sterile centrifuge tube and supplemented with FBS and antibiotics. Subsequently, osteoblasts with good growth status were selected to prepare a cell suspension. The cells were counted using an automatic cell counter (Countess 3, Thermo Fisher Scientific Co, USA), and the suspension density was adjusted to 1×10 4 / mL. The diluted cell suspension was inoculated into a 96-well plate at 100 μL per well, with a total of 20 wells per plate. Three plates were inoculated to ensure the reproducibility of the experiment. After inoculation, the 96-well plates were placed in a cell culture incubator for culture. After 24 hours, the cell adhesion was observed and the culture medium was changed. All groups received the corresponding bone cement extracts.
[0080] The cell counting kit-8 (CCK-8) (Aldrich, 96992) was used to evaluate the viability of MC3T3-E1 cells. At the predetermined time points (1, 3, and 5 days), the plates were taken out and the supernatant was aspirated. 100 μL of the medium containing the CCK-8 working solution was added to each well and incubated for 1 hour. Then, the absorbance (OD value) was measured at 450 nm using a microplate reader (Varioskan ALF, Thermo Fisher Scientific Co, USA), and the cell viability was calculated based on these OD values.
[0081] (3) Results of cell proliferation evaluation
[0082] The proliferation of MC3T3-E1 osteoblasts exposed to various bone cement extracts was evaluated by CCK-8 assay at days 1, 3, and 5 ( Figure 6 ). The results showed that the viability of MC3T3-E1 cells in the 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA groups exceeded 100% at all time points compared with pure PMMA. With the increase in the MoS2 content, the cell viability showed an upward trend. However, the viability of MC3T3-E1 cells in the 1% MoS2-PMMA group showed an upward trend compared with the pure PMMA group at days 1 and 3, but did not reach a statistically significant difference. This indicates that the MoS2-PMMA nanocomposite enhanced the proliferation of osteoblasts, and the effect was more significant at higher MoS2 concentrations.
[0083] (4) Alkaline phosphatase and alizarin red S staining
[0084] To evaluate the effects of the bone cement extracts on osteoblast differentiation and mineralization, the extracts prepared in (2) were used. The osteoblasts were seeded at 1×10 4Cells were seeded into 96-well plates at a density of cells / mL and cultured for 24 hours to promote cell adhesion. Subsequently, the culture medium was replaced with the corresponding bone cement extract. After 7 days and 14 days of culture, the culture medium was aspirated, and the osteoblasts were washed with phosphate buffer saline (PBS) (Aldrich, P2272), and then fixed with 4% paraformaldehyde (Aldrich, 158127) for 10 minutes. After fixation, the cells were washed again with PBS and stained with alkaline phosphatase (ALP) (Aldrich, APMB-RO) staining solution for 20 minutes to evaluate the degree of osteoblast differentiation. Similarly, on days 14 and 21 of culture, the culture medium was removed, the osteoblasts were washed with PBS and fixed with 4% paraformaldehyde. After fixation, the cells were washed with PBS and stained with 1% alizarin red S (ARS) (Aldrich, TMS-008) solution for 20 minutes to observe the formation of mineralized nodules. The stained cells were examined under a microscope to quantify the ALP activity and the number of mineralized nodules.
[0085] (5) Effects of MoS2-PMMA on osteoblast differentiation
[0086] ALP staining was performed on days 7 and 14 to investigate the effects of different MoS2-PMMA composite materials on osteoblast differentiation. The ALP-positive regions appeared as grayish-brown granular deposits in the cytoplasm. The ranking on day 7 was: 5% MoS2-PMMA, 3% MoS2-PMMA, 1% MoS2-PMMA, and pure PMMA ( Figure 7 ). Similar results were observed on day 14, and the ALP-positive regions of all composite materials were significantly increased compared to day 7. These results indicate that the MoS2-PMMA nanocomposite promoted the expression of ALP in osteoblasts, promoted their differentiation, and the effect was more significant at higher MoS2 concentrations.
[0087] (6) Effects of MoS2-PMMA on osteoblast maturation
[0088] The formation of mineralized nodules is a key marker of osteoblast maturation. ARS staining of osteoblasts cultured for 14 days showed that dark red mineralized nodules were present in all MoS2-PMMA co-culture groups, and the number of nodules increased significantly with the increase in MoS2 concentration. Specifically, the 5% MoS2-PMMA group had the largest number of nodules, followed by 3% MoS2-PMMA, 1% MoS2-PMMA, and pure PMMA ( Figure 8 ). Similar results were observed on day 21, and the number of nodules in the 1% MoS2-PMMA group was significantly increased compared to pure PMMA. These findings indicate that the MoS2-PMMA nanocomposite promoted the maturation of osteoblasts, manifested as an increase in the formation of mineralized nodules, and the effect was more significant at higher MoS2 concentrations.
[0089] Example 5 Antibacterial Properties of Bone Cement
[0090] (1) Microbial Contamination of Escherichia coli
[0091] The mixed contamination consisted of Escherichia coli (E. coli) (ATCC, 8739), which was previously cultured in BHI (Brain Heart Infusion) (BioMaxima, Lublin, Poland) agar broth at 37 °C for 24 hours. After incubation, one colony-forming unit (CFU) of each microorganism was transferred to 10 mL of BHI and shaken overnight under the same culture conditions. Before testing, the films were soaked in 70% ethanol for 1 hour and then washed in sterile PBS.
[0092] (2) Examination of Antibacterial Activity
[0093] After resuscitating Escherichia coli, a bacterial solution with a density of 110×10^7^ CFU / mL was prepared. Four groups of bone cement samples were respectively immersed in glass bottles containing 2 mL of the bacterial solution. Then these bottles were incubated in a shaking incubator at 37 °C for 5 minutes. Subsequently, 100 μL of the bacterial suspension was collected and spread on BHI agar medium. The medium was placed in a CO2-controlled incubator at 37 °C and incubated for 24 hours. After incubation, the number of bacterial colonies was counted using the quantitative plate method and photographed for record.
[0094] (3) Antibacterial Properties of MoS2-PMMA
[0095] The antibacterial test results of various MoS2-PMMA composite materials are as Figure 9 and Figure 10 shown. One-way ANOVA showed that the Escherichia coli colony counts in the 1% MoS2-PMMA, 3% MoS2-PMMA, and 5% MoS2-PMMA groups were significantly lower than those in the pure PMMA group (P value < 0.001). In PMMA bone cement, antibacterial activity was observed when the MoS2 concentration was 1%. As the MoS2 concentration increased, the colony count on BHI agar medium gradually decreased. The colony count in the 5% MoS2-PMMA group was the lowest. These results indicate that the antibacterial properties of PMMA bone cement are enhanced with the increase in MoS2 concentration, suggesting a positive correlation between MoS2 concentration and antibacterial effect.
Claims
1. A preparation method of a novel medical polymethylmethacrylate bone cement, characterized in that, It includes the following steps: (1) Dissolve PMMA powder in dimethyl sulfoxide to obtain a PMMA solution; (2) Add MoS2 nanosheets to the PMMA solution, stir the resulting mixture at 78 - 82 °C for 22 - 26 hours. After the stirring process ends, dry the mixture to obtain MoS2-PMMA nanocomposite. (3) Mix the MoS2-PMMA nanocomposite uniformly with MMA liquid, fill the resulting mixture into a mold and cure it to form a novel medical polymethyl methacrylate bone cement.
2. The preparation method according to claim 1, characterized in that, In step (1), the ratio of PMMA powder to dimethyl sulfoxide in the PMMA solution is 2 g : 50 mL.
3. The preparation method according to claim 1, wherein In step (1), dissolve PMMA powder in dimethyl sulfoxide and stir at room temperature for 24 hours to obtain a PMMA solution.
4. The preparation method according to claim 1, wherein In step (1), the synthesis method of the MoS2 nanosheets includes the following steps: Disperse MoS2 powder in N,N-dimethylformamide, and subject the mixture to ultrasonic treatment to form a black suspension; Subsequently, centrifuge the suspension in a high-speed centrifuge to collect the thinner MoS2 flakes; redisperse the obtained MoS2 flakes in N,N-dimethylformamide, add L-cysteine to the redispersed mixture, stir the mixture thoroughly to ensure uniform dispersion, and then age it at room temperature for 24 hours; After aging, centrifuge the mixture again to collect the precipitate, and wash the product with deionized water to obtain MoS2 nanosheets.
5. The preparation method according to claim 1, wherein, The concentration of the MoS2 powder in N,N-dimethylformamide is 5 mg / mL; the final concentration of L-cysteine in the redispersed mixture is 0.1 mg / mL; the time of the ultrasonic treatment is 12 hours; the centrifugation conditions are: centrifuge at 1200 rpm for 30 minutes; Centrifuge the suspension in a high-speed centrifuge to collect the light yellow supernatant containing the thinner MoS2 flakes; centrifuge the supernatant containing the thinner MoS2 flakes again; During the deionized water washing process, an additional centrifugation step at 12000 rpm is involved.
6. The preparation method according to claim 1, wherein In step (2), the weight percentage of the MoS2 nanosheets in the total amount of MoS2 nanosheets and PMMA powder is 1% - 5%.
7. The preparation method according to claim 1, characterized in that, In step (2), the specific operation of the drying is: pour the mixture into a petri dish and dry it under heating conditions to ensure complete evaporation of dimethyl sulfoxide.
8. The preparation method according to claim 1, characterized in that, In step (3), the ratio of the MoS2-PMMA nanocomposite to MMA liquid is 2 g : 1 mL.
9. The preparation method according to claim 1, characterized in that, In step (3), use a vortex mixer to mix the MoS2-PMMA nanocomposite and MMA liquid uniformly at room temperature; fill the resulting mixture into a mold and let it stand at room temperature for 25 - 35 min to cure and form.
10. A novel medical polymethyl methacrylate bone cement prepared by the preparation method described in any one of claims 1 - 9.